Socioeconomic aspects of families with children born exposed to the virus human immunodeficiency - Galvão, Marli Teresinha Gimeniz; Cunha, Gilmara Holanda da; Brito, Gizelly Castelo Branco; Gir, Elucir (Revista de Enfermagem UFPE on line, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> ABSTRACT Objective: to identify the socioeconomic aspects of families with children born exposed to human immunodeficiency virus. Method: cross-sectional, descriptive and quantitative study held in Fortaleza/CE/Brazil with 30 adults with human immunodeficiency virus/HIV. Data were collected through semi-structured instrument then tabulated, expressed in absolute and relative frequency tables. The research project was approved by the Research Ethics Committee of the hospital where the study was conducted, under protocol number 014/2007 with. Results: Of respondents, 96.6% were female. Of these families, 56.5% had at least two children. The main sources of income were informal employment (36.6%) and government assistance (33.4%), 73.4% were class "D" and "E", and 40% lived on less than minimum wage. Among families, 90.0% used public water supply and garbage was collected. Conclusion: most disadvantaged families is social class, which may contribute negatively in maintaining health. Descriptors: HIV; Acquired Immunodeficiency Syndrome; Family; Child. RESUMO Objetivo: identificar os aspectos socioeconômicos de famílias com filhos nascidos expostos ao vírus da imunodeficiência humana. Método: estudo transversal, descritivo e quantitativo, realizado em Fortaleza/CE/Brasil com 30 adultos com o vírus da imunodeficiência humana/HIV. Os dados foram coletados por meio de instrumento semiestruturado, em seguida tabulados, expressos em frequência absoluta e relativa nas tabelas. O projeto de pesquisa foi aprovado pelo Comitê de Ética em Pesquisa do hospital onde foi realizado o estudo,protocolo de número 014/2007. Resultados: dos respondentes, 96,6% eram do sexo feminino. Das famílias, 56,5% possuíam no mínimo dois filhos. As principais fontes de renda eram emprego informal (36,6%) e auxílio do governo (33,4%); 73,4% eram de classes “D” e “E”, e 40% conviviam com menos de um salário mínimo. Entre as famílias, 90,0% consumiam água de abastecimento público e o lixo era recolhido. Conclusão: a maioria das famílias constitui classe social desfavorecida, o que pode contribuir negativamente na manutenção da saúde. Descritores: HIV; Síndrome de Imunodeficiência Adquirida; Família; Criança. RESUMEN Objetivo: identificar los aspectos socioeconómicos de las familias con hijos nacidos expuestos al virus de la inmunodeficiencia humana. Método: estudio transversal descriptivo y cuantitativo, que tuvo lugar en Fortaleza-CE/Brasil con 30 adultos virus de la inmunodeficiencia humana-VIH. Los datos fueron recolectados a través de instrumento semi-estructurado, entonces tabulados, expresados en tablas de frecuencias absolutas y relativas. El proyecto de investigación fue aprobado por el Comité de Ética e Investigación del hospital donde se realizó el estudio, bajo el número de protocolo 014/2007. Resultados: del total de encuestados, el 96,6% eran mujeres. De estas familias, el 56,5% tenía al menos dos hijos. Las principales fuentes de ingresos son el empleo informal (36,6%) y la ayuda del gobierno (33,4%), el 73,4% eran de clase "D" y "E", y el 40% vive con menos de un salario mínimo. Entre las familias, el 90,0% utiliza abastecimiento público de agua y la basura se recogió. Conclusión: mayoría de las familias eran de clase social desfavorecida, que pueden contribuir negativamente en el mantenimiento de la salud. Descriptores: VIH; Síndrome de Inmunodeficiencia Adquirida; Familia; Niño.